Documenting Hidden Disabilities in Higher Education: Analysis of Recent Guidance From the Association on Higher Education and Disability (AHEAD). (June 2015) - Lovett, Benjamin J.; Nelson, Jason M.; Lindstrom, Will
Once students with disabilities leave high school, they must take proactive steps to document their disabilities to educational institutions or employers when requesting accommodations. The Association on Higher Education and Disability (AHEAD) has been the principal organization offering suggestions on documentation requirements, and AHEAD's recently revised guidance involves radical changes to the suggested requirements. AHEAD now recommends that students' self-reports and disability services professionals' impressions take precedence over external, objective records. This article reviews the relevant research to evaluate the evidence base for the revised guidance, finding it lacking in important ways as it applies to hidden disabilities (learning, cognitive, and psychiatric disabilities). The evidence supporting various sources of disability documentation is reviewed, and implications for policy and practice are discussed.